(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This research paper aims to assess the occupational stress among professional physicians whereas engaging the COVID-19 therapies in the research location. The Coronavirus pandemic in India is part of a worldwide pandemic caused by the brutally acute pulmonary syndrome virus. Physicians and the general public have expressed concern, grief, fear, and sadness as a result of the COVID-19 eruption. Doctors are more likely then the general population to suffer from a variety of mental diseases. All main and tertiary data were used in the inquiry. Secondary data was gathered on COVID-19 diseases and physician treatments. The important information obtained from clinicians relates to the COVID-19 treatment. The study has a sample size of 353. The responses were compiled into excel sheets, which were then imported into SPSS program versions 21 for analysis. For evaluating the framed hypothesis, the researchers used simple statistical distribution and a t-test. According to the study, the doctors used COVID-19 treatment for the initial 6 weeks, and % of the professionals had high stress levels. The study also found that when government hospital doctors started using COVID-19 therapy in hospitals, their work culture altered dramatically. According to the poll, government hospital doctors were unable to maintain a work-life balance. While participating in COVID 19 treatments in the research area, the doctor has had a significant impact on their personal lives and causes job stress.